2022
DOI: 10.1021/acs.jpclett.1c04028
|View full text |Cite
|
Sign up to set email alerts
|

Localized Excitonic Electroluminescence from Carbon Nanodots

Abstract: Localized excitons are expected to achieve high-performance electroluminescence and have been widely investigated in GaN-based light-emitting diodes (LEDs). Although carbon nanodot (CD) based LEDs have been achieved with the radiative recombination of electrons and holes, localized excitonic electroluminescence has been not reported before. In this Letter, localized excitonic electroluminescent devices have been fabricated using fluorescent CDs as an active layer. The CDs show strong localized excitonic yellow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 52 publications
(75 reference statements)
0
19
0
Order By: Relevance
“…Our results differ from those previously reported in the literature, in which the exciton absorption bands of CDs appear only within the ultraviolet region. 7,11,12,33 Here, we distinctly observe absorption in the visible range at 485 and 520 nm. In-depth investigations indicate that the 280–380 nm range is attributed to n–π* transitions, mainly including the oxygen functional groups of C–O and CO. 34 Peaks in the visible region at 380–800 nm are usually associated with the excitonic absorption band, indicating the high conjugation and high quality of the CDs.…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations
“…Our results differ from those previously reported in the literature, in which the exciton absorption bands of CDs appear only within the ultraviolet region. 7,11,12,33 Here, we distinctly observe absorption in the visible range at 485 and 520 nm. In-depth investigations indicate that the 280–380 nm range is attributed to n–π* transitions, mainly including the oxygen functional groups of C–O and CO. 34 Peaks in the visible region at 380–800 nm are usually associated with the excitonic absorption band, indicating the high conjugation and high quality of the CDs.…”
Section: Resultsmentioning
confidence: 66%
“…2a) of the CDs show a broad diffraction peak centered at around 2 θ = 21.5°, which is slightly shifted to a lower diffraction angle compared with the standard peak position (2 θ = 23°) of the (002) carbon crystal plane. 11 This may be due to the synergistic effect between graphitic carbons and amorphous carbons.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among such strategies, employing transition-metal dichalcogenides has attracted the attention of the research community. The most promising one is molybdenum-based structures that already demonstrated that they are more active than other materials to promote the charge transport in optoelectronic devices. , Using MoO 3 or MoS 2 nanostructures as a separate layer or additive in the PEDOT/PSS layer has been reported in various LEDs with different light-emitting layers such as perovskite NCs, Cd-based QDs, carbon dots, InP-based QDs, and even organic molecules . Nonetheless, in most cases, minimal attention has been dedicated to the synthesis of such MoO 3 or MoS 2 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%